Thermo-Mineral Baths in the First Half XIX Century: The Case of Ludwig Van Beethoven - Berezutsky, Vladimir; Berezutska, Maryna (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2020)
Background The great German composer Ludwig van Beethoven suffered almost all his life from progressive deafness and diseases of the digestive system. The state of his health strongly influenced his work. Balneotherapy is the only aspect of Beethoven’s disease history that has not yet been thoroughly studied. While water treatment in the first half of the XIX century was the most important part of the therapeutic arsenal of doctors and was actively used in the treatment of Beethoven.Objectives To study the use of thermo-mineral baths in the treatment of Ludwig van Beethoven in the first half of the XIX century.Methods Scopus, WebOfScience, MedLine and PubMed databases, electronic archives were searched without time restriction for information on the use of thermo-mineral baths in European spa resorts in the first half of the 19th century. An analysis was also made of Beethoven’s letters and the work of his most respected biographers in order to identify information about thermal-mineral baths in his treatment.Results Since 1796, Beethoven suffered chronic enterocolitis and progressive hearing impairment, since 1820 portalcirrhosis of the liver. Thermo-mineral baths were the main part of Beethovens treatment from 1799 until his death in 1827.Conclusions The Beethoven’s physicians appointed him a treatment that corresponded to the advanced achievements of balneology of the first half of the 19th century. The composer spent annually at spa resorts up to 6 months, water treatment became part of his life. Beethoven until the last days of his life sincerely believed in the healing power of thermo-mineral baths.Hintergrund Der größte Deutscher Komponist Ludwig van Beethoven litt fast sein ganzes Leben lang an aggressiver Taubheit und an Krankheiten der Verdauungsorgane. Der Zustand seiner Gesundheit beeinflusste sehr stark sein Schaffensvermögen. Balneotherapie ist der einzige Aspekt in Beethovens Krankengeschichte, welche noch nicht ausreichend erforscht wurde. Während Balneotherapie in der ersten Hälfte des XIX. Jahrhunderts der wichtigste Teil des therapeutischen Arsenals der Ärzte war und aktiv bei der Behandlung von Beethoven eingesetzt wurde.Ziele Untersuchung der Verwendung von Thermomineralbädern bei der Behandlung von Ludwig van Beethoven Methoden In den Datenbanken Scopus, WebOfScience, MedLine und PubMed wurden elektronische Archive ohne zeitliche Einschränkung nach Informationen über die Nutzung von Thermomineralbädern in europäischen Kurorten in der ersten Hälfte des XIX. Jahrhunderts durchsucht. Außerdem wurden die Briefe Beethovens und die Arbeiten seiner angesehensten Biografen analysiert, um Informationen über Thermomineralbäder in seiner Behandlung zu ermitteln.Ergebnisse Seit 1796 litt Beethoven an chronischerEnterokolitis und fortschreitender Schwerhrigkeit, seit 1820 portale Leberzirrhose. Thermomineralbder waren von 1799bis zu Beethovens Tod im Jahr 1827 der Hauptbestandteil seiner Behandlung.Schlussfolgerungen Die Ärzte Beethovens verordneten ihm eine Behandlung, die den fortschrittlichen Errungenschaften der Balneologie der ersten Hälfte des XIX. Jahrhunderts entsprach. Der Komponist verbrachte jährlich bis zu 6 Monate in Kurorten, die Wasserbehandlung wurde zum Teil seines Lebens. Beethoven glaubte bis in die letzten Tage seines Lebens aufrichtig an die Heilkraft der Thermomineralbäde.
Keywords: thermo-mineral baths; history of balneotherapy; history of spa resorts in Europe; Ludwig van Beethoven